A estrutura dramática dos diálogos sobre religião natural de Hume e o problema do ateísmo - Luis Felipe Lopes (2018)
This thesis deals with Hume`s enquiry, in Dialogues, concerning the issue of the existence of God. It is argued that the aforesaid work fits into an atheistic perspective, since an alternative explanatory theory to theism is proposed. For that manner, we will investigate the intellectual and stylistic path of the work, identifying the authors philosophy in relation to characters, to analyze his restrictions on the design and cosmology proofs. Therefore, Hume proposes that evoking God as an explanatory condition of natural world and morality lacks justification, and it is possible, according to his naturalism and skepticism, an alternative explanatory theory in accordance with the human nature, namely: atheism as a kind of Godless philosophy